Peran Persepsi Daya Tarik Wisata dalam Memediasi Pengaruh Paparan Konten TikTok terhadap Minat Berkunjung Wisatawan Domestik di Pantai Sawarna Kabupaten Lebak - Eman Diantoro; Yayuk Karliena; Ahmad Najiyullah; Tita Oktaviani; Azimi Faqqihuddin Arsyad (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the mediating role of Perceived Tourist Attractions in the relationship between TikTok Content Exposure and Domestic Tourist Intention to Visit Sawarna Beach, Lebak Regency. The background of this study is the phenomenon of digital virality that does not always translate into actual visits, as well as the gap between destination images on social media and the reality on the ground. Using the Stimulus-Organism-Response (S-O-R) theoretical framework, this study examines the psychological mechanisms underlying tourist decisions. The research method used was quantitative with a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach on 377 respondents who are active TikTok users.The results showed four main findings: (1) Exposure to TikTok Content has a very strong positive influence on Perceived Tourist Attractions (β=0.763), but (2) it does not have a significant direct influence on Visit Intentions (β=0.035); (3) Perceived Tourist Attractions has a very strong positive influence on Visit Intentions (β=0.750); (4) It was found that Perception of Tourist Attraction fully mediated the relationship between TikTok Content Exposure and Visit Intention, with a VAF value of 94.2%.